2003
DOI: 10.1002/ffj.1177
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition variability of the essential oil of Conyza canadensis Cronq.

Abstract: The essential oils from different botanical parts (herb, leaves, flowers, stems, roots) of Conyza canadensis Cronq. were analysed at various ontogenesis phases. R-(+)-limonene and trans-α-bergamotene were the main constituents of the herb, leaf and flower oil at all phases of vegetation. The early flowering phases are the best time for harvesting C. canadensis herb, because the oil yield is the highest (0.7-0.8%) and its chemical composition is constant (limonene 80-81%, trans-α-bergamotene 6-8%). Limonene was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…This was not unexpected, because the composition of C. canadensis essential oil can vary according to the collection site and the growth phase of the plant. 17,18 The chloroform fraction, with fewer concomitant compounds, was submitted to preparative flash chromatography in order to isolate the analytes of interest. The NMR spectra of the isolated compounds 1 and 2 agreed with published data, except for the C-8 and C-9 carbons of compound 1.…”
Section: Resultsmentioning
confidence: 99%
“…This was not unexpected, because the composition of C. canadensis essential oil can vary according to the collection site and the growth phase of the plant. 17,18 The chloroform fraction, with fewer concomitant compounds, was submitted to preparative flash chromatography in order to isolate the analytes of interest. The NMR spectra of the isolated compounds 1 and 2 agreed with published data, except for the C-8 and C-9 carbons of compound 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Barbosa and coworkers (2005) found that C. bonarensis contains matricaria methyl ether and manool, along with limonene and carvone as the main volatiles metabolites. Hrutfiord et al (1988) and Lis et al (2002) described the presence of trans-a-bergamotene, cis-a-bergamotene, (Z)-b-farnesene and R-(þ)-limonene, together with b-pinene and myrcene for C. canadensis. Finally, Ndiege et al (2005) identified five major components including limonene, 2-methyl-5-(methylethyl)-2-cyclohexen-1-ol, 1,8-cineol, perillaldehyde and perillalcohol in the oil of C. newii.…”
Section: Discussionmentioning
confidence: 99%
“…The layers were separated and the water layer was extracted with hexane (3 × 20 ml). The collected organic layers were washed with water and dried over MgSO 4 . After decantation from the drying agent, the solvent was evaporated in a rotary evaporator.…”
Section: Synthesis Of Isomeric C 14 2-alkylalkanalsmentioning
confidence: 99%
“…3,4 Octanal has been found in lavender essential oil; 1 nonanal in small concentrations (0.02%) in essential oils obtained from rose, root of iris and the plant Solidago virgaurea; 1,5 decanal in nerol; 6 undecanal in the essential oil of Citrus spp. and of the plant Fortunella marginata; 6 dodecanal in the essential oil of pine needles and of the plants Chamaecyparis lawsonia and Anthemis altissima L. 1,6,7 The presence of tetradecanal has also been noted in the essential oil of Salvia nemorosa.…”
Section: Introductionmentioning
confidence: 99%